Designing Decellularized Extracellular Matrix‐Based Bioinks for 3D Bioprinting. Issue 24 (21st July 2020) - Abaci, Alperen; Guvendiren, Murat
Abstract: 3D bioprinting is an emerging technology to fabricate tissues and organs by precisely positioning cells into 3D structures using printable cell‐laden formulations known as bioinks. Various bioinks are utilized in 3D bioprinting applications; however, developing the perfect bioink to fabricate constructs with biomimetic microenvironment and mechanical properties that are similar to native tissues is a challenging task. In recent years, decellularized extracellular matrix (dECM)‐based bioinks have received an increasing attention in 3D bioprinting applications, since they are derived from native tissues and possess unique, complex tissue‐specific biochemical properties. This review focuses on designing dECM‐based bioinks for tissue and organ bioprinting, including commonly used decellularization and decellularized tissue characterization methods, bioink formulation and characterization, applications of dECM‐based bioinks, and most recent advancements in dECM‐based bioink design. Abstract : Current developments and 3D cell printing applications of dECM‐based bioinks are discussed in this review article. The article also discusses the current challenges of biofabrication of tissue models using dECM‐based bioinks and future prospects of utilization of dECM‐based bioinks to fabricate advanced tissue models to mimic the native tissue.